Dynamics of scientific communication: an application to science funding policy - (:unkn) unknown (My University, 1977)
[en] Some of the major problems associated with creteria for funding policies can be grouped into four categories, according to whether they refer to: a) division of available funds among the different areas of science; b) detection of oncoming "crisis" in a given area; c) which scientists should be supported, within an area; d) which communication channels (journals) should be supported, also within an area. These problems can be investigated trough the literature of science - one of the most tangible outputs of the act of scientific creation. A model was devised, capable of helping the decision making process concerning the problems mentioned above. The model is based on static and dynamic analyses of the literature. Both kinds of analyses used bibliometric laws and techniques. Lotka's, Bradford-Zipf's and citation counts were used for the static analyses; The Epidemic Model and The Resource Limited Growth Model were used for the dynamic.
Keywords: Ciêcia da Informação; Bibliometria; Transferência de informação; Informação científica e tecnológica; Custos